1995
DOI: 10.1101/gad.9.9.1046
|View full text |Cite
|
Sign up to set email alerts
|

Raf1 interaction with Cdc25 phosphatase ties mitogenic signal transduction to cell cycle activation.

Abstract: The Ras and Rafl proto-oncogenes transduce extracellular signals that promote cell growth. Cdc25 phosphatases activate the cell division cycle by dephosphorylation of critical threonine and tyrosine residues within the cyclin-dependent kinases. We show here that Cdc25 phosphatase associates with rafl in somatic mammalian cells and in meiotic frog oocytes. Furthermore, Cdc25 phosphatase can be activated in vitro in a Rafl-dependent manner. We suggest that activation of the cell cycle by the Ras/Rafl pathways mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
141
1
2

Year Published

1997
1997
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(151 citation statements)
references
References 93 publications
(118 reference statements)
6
141
1
2
Order By: Relevance
“…The link between ras and the cell cycle has been strengthened by more recent reports showing that activated ras induces cyclin D 1 in NIH3T3 cells (Winston et al, 1996;Filmus et al, 1994) and that the raf kinase, a putative downstream target of ras, interacts with and regulates the activity of cdc25 (Galaktionov et al, 1995), a phosphatase involved in regulation of cdc2, an essential G 2 /M kinase. However, the direct roles of ras in regulation of the very complex cell cycle machinery is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…The link between ras and the cell cycle has been strengthened by more recent reports showing that activated ras induces cyclin D 1 in NIH3T3 cells (Winston et al, 1996;Filmus et al, 1994) and that the raf kinase, a putative downstream target of ras, interacts with and regulates the activity of cdc25 (Galaktionov et al, 1995), a phosphatase involved in regulation of cdc2, an essential G 2 /M kinase. However, the direct roles of ras in regulation of the very complex cell cycle machinery is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that these interactions might link the signal transduction machinery to cell cycle activation (Conklin et al, 1995;Galaktionov et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Since Cdc25A has transforming activity as well (Galaktionov et al, 1995a), Cdc25A may be one of the key molecules that transduce the signal Interestingly, Cdc25A contains a peptide sequence that can be phosphorylated by Pim-1 kinase (TM, unpublished observation). It would therefore be possible that Pim-1 stimulates c-Myc-mediated apoptosis through the phosphorylation and activation of the phosphatase activity of Cdc25A, similar to another serine/threonine kinase, Raf-1, which has been shown to bind and activate the phosphatase activity of Cdc25A (Galaktionov et al, 1995b). We are now performing experiments to test this idea.…”
Section: Discussionmentioning
confidence: 99%